2015
DOI: 10.2139/ssrn.2574816
|View full text |Cite
|
Sign up to set email alerts
|

Bank Ownership Structure, Lending Corruption and the Regulatory Environment

Abstract: Where a licence is displayed above, please note the terms and conditions of the licence govern your use of this document. When citing, please reference the published version. Take down policy While the University of Birmingham exercises care and attention in making items available there are rare occasions when an item has been uploaded in error or has been deemed to be commercially or otherwise sensitive.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
13
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(15 citation statements)
references
References 43 publications
2
13
0
Order By: Relevance
“…Meanwhile, research had shown that corruption in underdeveloped countries is a primary obstacle for businesspeople to access the credit. In the type of bank ownership, the countries that have more state-owned banks or more family-owned banks, lending corruption is greater (Barry et al, 2016). In contrast, Barth et al (2009) found that corruption is weaker in the state-owned banks along with the sharing information and competition in bank lending (Barth et al, 2009).…”
Section: Corruption and Bank Soundnessmentioning
confidence: 97%
“…Meanwhile, research had shown that corruption in underdeveloped countries is a primary obstacle for businesspeople to access the credit. In the type of bank ownership, the countries that have more state-owned banks or more family-owned banks, lending corruption is greater (Barry et al, 2016). In contrast, Barth et al (2009) found that corruption is weaker in the state-owned banks along with the sharing information and competition in bank lending (Barth et al, 2009).…”
Section: Corruption and Bank Soundnessmentioning
confidence: 97%
“…Authors attribute this finding to the fact that the financial institutions or creditors closely monitor borrowers' activities and hence potentially reduces their level of corruption. Similarly, Barry, Lepetit, and Strobel (2016) investigate the role of bank ownership on bank lending corruption by accounting other determinants in the model such as regulatory environment and the level of economic development. The findings indicate that lending corruption is significantly higher in circumstances where a higher proportion of credit comes from the state-owned or family-owned banks.…”
Section: Introductionmentioning
confidence: 99%
“…The disposition of the banks, in aiding and abetting corrupt government officials to steal public funds and providing a haven for them to hide their illicit fund or legalise the proceed of corruption because of their drive for profit is the motivation for this study. Previous studies have examined bank lending corruption and various dimension and consequences (Barth et al , 2016; Barry et al , 2016; and Jiang et al , 2018). The uniqueness of this study from previous studies on corruption in the banking sector is that it fills the gap in the literature on the other side (i.e.…”
Section: Resultsmentioning
confidence: 99%
“…The banking system in such a situation will not be able to perform its primary function of efficient allocation of scarce resources. Barry et al (2016) examined the influence of bank ownership structure, regulatory environment and economic development on bank lending corruption. The findings revealed that corruption was higher when a state-owned bank or family-owned bank provided a higher proportion of credit to the economy.…”
Section: Literature Reviewmentioning
confidence: 99%